1992
DOI: 10.1177/0148607192016006525
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Compared With Intermittent Tube Feeding in the Elderly

Abstract: The methods of continuous (C) and intermittent (I) nasogastric tube feedings in 60 patients, 54 men and 6 women, with a mean age of 72 +/- 9 years were compared in terms of number of complications, staff time used, and caloric intake. Patients were randomly assigned between these two methods and followed for 7 days. Diarrhea, aspiration pneumonia, clogged tubes, and self-extubation were observed in both groups. Diarrhea was significantly more frequent (96% of 30 patients) in the I group than the C group (66% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 11 publications
2
50
1
Order By: Relevance
“…9 -11 The increased frequency and duration of diarrhea observed by Ciocon et al in patients receiving intermittent feedings was not demonstrated in our patients. 11 The difference may be a result of the age difference between the two populations investigated, because our intermittent group feeding regimens were identical.…”
Section: Discussionmentioning
confidence: 99%
“…9 -11 The increased frequency and duration of diarrhea observed by Ciocon et al in patients receiving intermittent feedings was not demonstrated in our patients. 11 The difference may be a result of the age difference between the two populations investigated, because our intermittent group feeding regimens were identical.…”
Section: Discussionmentioning
confidence: 99%
“…A lower incidence of feeding tube obstruction occurs with intermittent than with continuous tube feeding [3]. This observation presumably is due to delivery of a greater formula volume at a higher pressure.…”
Section: Discussionmentioning
confidence: 93%
“…Tube feeding methods have been studied and compared in several studies, mostly for patients in a hospital setting [37,38] and in healthy volunteers [12,39] . These studies have mainly focused on diarrhea and appetite, and no consensus has been reached about one preferable method.…”
Section: Discussionmentioning
confidence: 99%